Pengembangan Brosur Kesehatan Masyarakat Berbasis Pengobatan Herbal - Riska, Irma Wati (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2024)
Brochures are one of the media used to convey information. Brochures are also defined as paper documents which are usually used as advertising or promotions. According to the Big Indonesian Dictionary (BID), brochures are defined as written information material about a problem that is prepared in a systematic way. This system is in the form of a print, which only consists of a few pages that can be folded without being bound. This research aims to develop a public health brochure based on herbal medicine. This type of research is development research. The research sample used was 15 people from Surabaya Village, East Sakra Subdistrict, East Lombok Regency. Data collection techniques are validation and readability testing. The data analysis technique used is the percentage technique. The research results showed that the herbal medicine-based public health brochure was based on content/material experts (3.8), language experts (3.7), and display experts (3.75), as well as the average score of the public readability test namely (3.7), which is categorized as not requiring revision or suitable for use.